E-Business Higher Education and Intelligence Applications - Wu, Robert M.X; Mircea, Marinela (IntechOpen, 2021)
This book provides the latest viewpoints of scientific research in the field of e-business. It is organized into three sections: "Higher Education and Digital Economy Development", "Artificial Intelligence in E-Business", and "Business Intelligence Applications". Chapters focus on China's higher education in e-commerce, digital economy development, natural language processing applications in business, Information Technology Governance, Risk and Compliance (IT GRC), business intelligence, and more.